2011
DOI: 10.1021/la104654p
|View full text |Cite
|
Sign up to set email alerts
|

Azobenzene-Containing Triazatriangulenium Adlayers on Au(111): Structural and Spectroscopic Characterization

Abstract: Adlayers of different azobenzene-functionalized derivatives of the triazatriangulenium (TATA) platform on Au(111) surfaces were studied by scanning tunneling microscopy (STM), X-ray photoelectron spectroscopy (XPS), gap-mode surface-enhanced Raman spectroscopy (gap-mode SERS), and cyclic voltammetry (CV). The chemical composition of the adlayers is in good agreement with the molecular structure, i.e., different chemical groups attached to the azobenzene functionality were identified. Furthermore, the presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
74
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(88 citation statements)
references
References 76 publications
11
74
2
Order By: Relevance
“…2a and b, inset) reveal the triangular shape of the molecules, indicating a planar adsorption of the bare and vertically functionalized platforms and a uniform orientation of the molecules. As in our previous studies of TATA adlayers, 3,5 no indications for the BF 4 À counter ions were found. Most probably, these are not coadsorbed on the surface, which can be explained by charge transfer from the substrate to the adsorbate molecules.…”
supporting
confidence: 64%
See 1 more Smart Citation
“…2a and b, inset) reveal the triangular shape of the molecules, indicating a planar adsorption of the bare and vertically functionalized platforms and a uniform orientation of the molecules. As in our previous studies of TATA adlayers, 3,5 no indications for the BF 4 À counter ions were found. Most probably, these are not coadsorbed on the surface, which can be explained by charge transfer from the substrate to the adsorbate molecules.…”
supporting
confidence: 64%
“…1 We recently introduced the platform approach for preparation of wellordered adlayers with freestanding functional groups on metal surfaces and illustrated its feasibility by employing derivatives of the triazatriangulenium (TATA) ion. [2][3][4][5] The triangularshaped TATA platform can be functionalized either vertically at the central carbon or laterally at the outer nitrogen atoms and thus serves as a chemically very modular and versatile template. Up to now, more than 30 TATA derivatives with different functional groups have been synthesized.…”
mentioning
confidence: 99%
“…Although these arguments, supported by literature data that confirm the Ag-supported photocatalyzed formation of azo bonds from primary amines, [64][65][66][67][68] would suggest a straightforward association of this new component to the azo nitrogen, we note that the expected BE for a simply physisorbed azo group should be higher than the observed one. [69][70][71][72] Chemisorption on metal surfaces generally induces a BE redshift [73] as consequence of the electron donation from the surface. [74] In particular, chemisorption through the central azo bridge at the metal surface [75] can reduce the observed binding energy to 398 eV.…”
Section: à2mentioning
confidence: 99%
“…The bands at 1,600 and 1,510 cm −1 are assigned to ring breathing of aromatic ring and appears in the spectra of modified materials. While the bands at 1,410 and 1,440 cm −1 are assigned to –N=N‐ bonds and also occur only in the modified zeolite .…”
Section: Resultsmentioning
confidence: 99%